The Impact Of Using Animated Videos On Students' Listening Skills In Arabic Language Learning - islamiah, zaffa; Zainal Arifin Ahmad (Hasanuddin University, 2025)
This study addresses one of the key challenges in Arabic listening (istima') instruction, where students often face difficulties in understanding implied meanings within conversations. Traditional teaching methods have contributed to a lack of student interest, highlighting the need for innovation in teaching media. This research aims to explore the impact of using animated videos as a medium in listening instruction from a qualitative perspective. Utilizing a qualitative research approach, the study focused on first-semester students in the Arabic Language Education Department at UIN Sunan Kalijaga. Data collection was conducted through classroom observations, in-depth interviews with students, and reflective feedback sessions, allowing the researcher to capture the experiences and perceptions of students in detail. The data was then analyzed thematically, revealing patterns of increased student engagement, motivation, and comprehension. The findings show that animated videos helped students better understand complex concepts in listening activities by providing visual support that complemented the audio elements. Many students reported that the combination of visual and auditory information made the content more accessible and engaging. Furthermore, students expressed that the videos helped bridge the gap between theoretical instruction and real-world application, making the learning experience more meaningful. Despite some challenges, such as limited technological resources, students' feedback and observations demonstrated that animated videos effectively contributed to improving their listening skills. This study underscores the potential of animated media to enhance the learning experience by fostering deeper understanding and engagement in Arabic listening instruction.